Hitherto unreported Agaricus species of Central India - ALKA KARWA; MAHENDRA K. RAI (Smujo International, 2010)
Abstract. Karwa A, Rai MK. 2010. Hitherto unreported Agaricus species of Central India. Nusantara Bioscience 2: 141-145. Melghat forest region from Central India was surveyed for occurrence of medicinal and culinary mushrooms during the years 2005-2008. Out of total 153 species, ten species of Agaricus were recorded from different localities. Of these, seven species namely Agaricus bitorquis, A. subrufescens, A. augustus, A. placomyces, A. essettei, A. basioanolosus and Agaricus sp. nov (a new species) are being reported for the first time from the region. The commercial button mushroom Agaricus bisporus lacks good breeding characters due to its bisporic nature. These wild cousins of the button mushroom can definitely prove to be a good source of genetic manipulations to the existing strains and also to develop new strains with improved characters.